Personalized Medicine for PLA2R1-Related Membranous Nephropathy: A Multicenter Randomized Control Trial - Brglez, Vesna; Boyer-Suavet, Sonia; Zorzi, Kévin; Fernandez, Céline; Fontas, Eric; Esnault, Vincent; Seitz-Polski, Barbara (Frontiers in Medicine, 2020)
Membranous Nephropathy (MN) is a rare autoimmune disease related to PLA2R1 antibodies in 70% of cases. One third of patients enter in spontaneous remission. PLA2R1 epitopes in MN have been characterized in four different domains of PLA2R1 and a mechanism of epitope spreading from the immunodominant CysR domain to CTLD1 and/or CTLD7 and/or CTLD8 domains has been associated with poor prognosis. Epitope spreading could predict spontaneous remission (45% in non spreader patients vs 0.05% in spreader patients). The comparison of different regimens of rituximab dosing showed that: (i) early remission rate depends on rituximab dosing, (ii) low dose could be enough for patients with anti-PLA2R1 activity restricted to CysR, (iii) high dose may be required for spreader patients. This study aims to evaluate the efficacy of personalized treatment in PLA2R1-related MN depending on the epitope spreading status, in comparison to the established GEMRITUX protocol. A multicenter, randomized, controlled, prospective clinical trial will be conducted in 22 French hospitals. Sixty-four consecutive patients with PLA2R1-related MN will be randomly assigned to either the control group following the GEMRITUX protocol (symptomatic treatment for six months, if the nephrotic syndrome (NS) persists at month-6, two 375 mg/m2 rituximab infusions at one week interval) or the personalized treatment group (patients with no epitope spreading at month-0 will be treated with symptomatic treatment for six months, if NS persists at month-6, two 375 mg/m2 rituximab infusions at one week interval; patients with epitope spreading at month-0 or month-6 with persistent NS will be treated immediately with two 1 g rituximab infusions at two week interval). The primary study outcome is the rate of clinical remission at month-12. The secondary outcomes include complete and partial remissions, immunological remissions, relapses, proteinuria, albuminuria, serum creatinine, eGFR, PLA2R1 antibody titers, severe infections, lymphocyte counts and lymphocyte phenotype, residual rituximab levels at month-3 and neutralizing anti-rituximab antibodies at month-6and -12 after rituximab treatment. The results of this trial will confirm whether personalized treatment of PLA2R1-driven nephrotic MN is more efficient to induce clinical remission than the established GEMRITUX protocol, and may thus contribute to improved remission rates and reduced relapse rates.